DISTRIBUSI SPASIAL, KARAKTERISTIK HABITAT DAN KARAKTERISTIK POPULASI POHON NYAMPLUNG (Calophyllum inophyllum L.) DI PESISIR PANTAI KABUPATEN PADANG PARIAMAN - Silvia Ayunda; Reki Kardiman; Irma Leilani Eka Putri; Filza Yulina Ade (Universitas Tribhuwana Tunggadewi, 2025)
Nyamplung (Calophyllum inophyllum L.) is a coastal plant species that plays an important ecological role in protecting coastal areas from abrasion, reduce the impact of sea winds, and maintain the stability of coastal environments, while the tree is economically potential as vegetable oil sources for biodiesel. In Padang Pariaman Regency, Nyamplung is also knows as Pinago, the trees are found growing in the coastal areas, both naturally and through planting, but it is still remain unknown the current spatial distribution and the local habitat conditions. This study aimed to investigate the spatial distribution and habitat characteristics of Nyamplung in the coastal area of Padang Pariaman Regency. Field observations were conducted for recording coordinates location of each Nyamplung tree, measuring the diameter at breast height (DBH) and canopy cover, and determining habitat characteristics. The spatial distribution was analyzed using ArcGIS, while the habitat conditions and the population structure were analyzed in terms of linear regression. The results showed that Nyamplung was distributed partly or clustered at three specific site in the coastline. Most of the site was sandy habitat with very thin layer of top soil and the trees were moslty exposed to full sunlight. The trees were varied in size, ranged from 2-62 cm dbh, with crown cover ranged from 5-600 m2, and these two variables were positively correlated. This study showed a limited number of Nyamplung trees in the coastal of Padang Pariaman, with less damage of community to canopy. Planting of Nyamplung in this area for a wider positive impact.